The relationship between stock market development and economic growth in Africa - Mkhize, Siyanda (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2019)
Over the years there has been a substantial increase in the number of African stock markets. This has generated much interest from local and foreign investors, as these stock markets have had high returns. These conditions have created an interesting scenario for investigating the relationship between stock market development and economic growth. However, this opportunity has largely been neglected as the research on African stock market development is limited in developing economies relative to research conducted in developed countries. Furthermore, the research that has been conducted on the relationship between stock market development and economic growth in Africa, has generated inconclusive and conflicting results, in addition to this, the institutional quality of African countries is disregarded in most studies when the stock market development and economic growth nexus is analysed. Therefore, this study aims to explore the relationship between stock market development and economic growth, incorporating institution variables to account for the institutional quality of African countries to provide clarity in this context. To achieve this, two sets of research hypotheses were created the first set aims to determine whether stock development has an influence on economic growth. The second set is to determine if there is any causal relationship between stock market development and economic growth. The study utilizes System Generalized Method of Moments models to examine the effect of stock market development on economic growth, in 18 African countries for the period 2003- 2016. The results indicate that market capitalization has a positive influence on economic growth whilst, contrastingly liquidity in the form of value traded has a negative effect on economic growth. The study further analyses the causal relationship between stock market development and economic growth, by employing the recently developed PVAR-Granger causality test. However, before this is done several Pedroni cointegration tests were first conducted to establish whether a long-term relationship exists between stock market development and economic growth, which revealed that no strong evidence of cointegration exists necessitating the use of a PVAR-Granger causality test. The PVAR-Granger causality test reveals that stock market development granger causes economic growth, irrespective of the stock market development measure used and there is no feedback effect from economic growth. The unilateral causality established in this study flowing from stock market development to economic growth supports the supply-leading hypothesis. The overall results of this study demonstrate that there is ambiguity on the impact of stock market development on economic growth, as the measures of stock market development have contrasting impacts on economic growth. The size component of stock market development in the form of market capitalization has positive influence whilst, liquidity in form of total value traded has a negative effect. However, the causal relationship is clearly shown to be unilaterally flowing from stock market development to economic growth.
Keywords: Stock exchanges -- Africa; Africa -- Economic conditions -- 21st century; Economic development -- Africa -- 21st century; Capital market -- Africa; Finance -- Africa -- 21st century; Developing countries -- Economic conditions -- 21st century